2019
DOI: 10.1042/bsr20181377
|View full text |Cite
|
Sign up to set email alerts
|

The role of miRNAs in the invasion and metastasis of cervical cancer

Abstract: Cervical cancer (CC) with early metastasis of the primary tumor results in poor prognosis and poor therapeutic outcomes. MicroRNAs (miRNAs) are small, noncoding RNA molecules that play a substantial role in regulating gene expression post-transcriptionally and influence the development and progression of tumors. Numerous studies have discovered that miRNAs play significant roles in the invasion and metastasis of CC by affecting specific pathways, including Notch, Wnt/β-catenin, and phosphoinositide-3 kinase (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 167 publications
(200 reference statements)
1
47
0
1
Order By: Relevance
“…miRNAs have regularly been found to be dysregulated in cervical cancer (31). Indeed, the dysregulation of miRNAs has been reported to contribute to a number of processes associated with cancer pathophysiology, including cell proliferation, cell cycle, apoptosis, epithelial-mesenchymal transition, metastasis, angiogenesis and resistance to chemoand radiotherapy (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have regularly been found to be dysregulated in cervical cancer (31). Indeed, the dysregulation of miRNAs has been reported to contribute to a number of processes associated with cancer pathophysiology, including cell proliferation, cell cycle, apoptosis, epithelial-mesenchymal transition, metastasis, angiogenesis and resistance to chemoand radiotherapy (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Even though E1, E2, L1 and L2 are always encountered in all HPVs, the other genes may vary (Stubenrauch et al, 2007;Nobre et al, 2009). The major oncogenes are considered to be E5, E6 and E7, which are also known for altering a variety of signaling pathways, such as Wnt, Notch, PI3K/Akt, MAPK, IFN and NF-κB and others (Gupta et al, 2018;Xu et al, 2018;Wang and Chen, 2019). However, studies have demonstrated that the HPV infection could alter the interaction between miRNAs and some of these pathways.…”
Section: Microrna Signaling In Hpv Infectionmentioning
confidence: 99%
“…They may act as tumor suppressors or oncogenes by regulating the expression of various target genes (2,3). MiR-21 has been reported to be associated with a wide variety of human cancers, including cervical cancer (4,5). The upregulation of miR-21 has been observed in cervical cancer cell lines and clinical specimens (6,7).…”
Section: Introductionmentioning
confidence: 99%